Milk production of Criollas and Anglo-Nubian does in Loja, Ecuador - Pes?ntez, Manuel T.; Hern?ndez, Arelis (Cuban Journal of Agricultural Science, 2014)
In order to characterize the daily milk production (1999-2001) and to determine the influence of several environmental effects, records of 99 lactations from 47 Criollas does, and 45 lactations from 28 Anglo-Nubian does were used in the ?Estaci?n Experimental de Zapotepamba? from Loja province, Ecuador. The daily milk production was weighed every fifteen days for four months, with a total of eight weighs per animal and the production of accumulated milk at 120 d was determined. The feeding consisted on browsing and free grazing. The she-goats for production were also fed with 200 g/animal/d of a concentrate with 14 % of CP. The weaning of the kids was between 45 to 50 d after the parturition, with mean weights of 13.6 kg. A mixed model was applied to study the effects of the genotype (Criolla and Anglo-Nubian), doe nestled in the genotype, number of parturition (3), parturition season (rainy and dry) and the interactions genotype x number of parturitions and genotype x season of parturition. The average of the daily milk production of the Criollas does was of 0.45 ? 0.22 kg/animal/d, and for the Anglo-Nubian does was of 0.76 ? 0.22 kg/animal/d. The lowest productions in both genotypes were obtained in the first parturition. It can be concluded that the daily milk production of Anglo-Nubian and Criolla does was affected by the effects of genotype and number of parturition and that the milk production in Anglo-Nubian does was superior to the Criollas by 0.30 kg/animal/d. Key words: Criollas and Anglo-Nubian does, environmental effects, daily milk production